Unraveling Community Dynamics: Management Strategies for SME Development - Suarlin, Suarlin (Golden Ratio of Community Services and Dedication, 2023)
This study explores management strategies for Small and Medium Enterprises (SMEs) development and community resilience. Employing a qualitative research approach, the literature on SME development and community dynamics is systematically reviewed. The research method involves a comprehensive literature search, data extraction, and thematic analysis to uncover patterns, themes, and relationships. Key findings indicate that fostering collaboration, resource mobilization, and access to finance are fundamental management strategies for SME growth and sustainability. Collective action mechanisms, industry clustering, and policy interventions emerge as effective approaches to promote SME development and industry specialization within communities. The study underscores the importance of strategic management strategies in unlocking the growth potential of SMEs and contributing to community development and economic resilience. The synthesis of literature provides insights into the nuanced interactions between management strategies, community dynamics, and SME performance. The findings have implications for policymakers, practitioners, and researchers in the field of SME development and community economics.